2004
DOI: 10.1007/s00464-003-8137-6
|View full text |Cite
|
Sign up to set email alerts
|

Plastic wound protectors do not affect wound infection rates following laparoscopic-assisted colectomy

Abstract: The wound protector, although useful for mechanical retraction of small wounds, does not significantly diminish the rate of wound infection at the bowel resection/anastomotic site. Patients undergoing elective resection for inflammatory processes have higher infection rates than patients undergoing laparoscopic-assisted colectomy for polyps or cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…Consequently, the net length of time during which a small laparotomy wound is made is shorter in LS than in OS, and this may possibly have a favorable influence on wound healing after LS. Regarding the plastic wound protectors used to prevent port site recurrence, Kercher et al [10] reported that a wound protector did not significantly diminish the rate of WI at the extraction site; however, it is currently unthinkable to perform LS for malignant diseases without a plastic wound protector, and the significance of plastic wound protectors in terms of WI may need to be investigated in benign diseases.…”
Section: Discussionmentioning
confidence: 98%
“…Consequently, the net length of time during which a small laparotomy wound is made is shorter in LS than in OS, and this may possibly have a favorable influence on wound healing after LS. Regarding the plastic wound protectors used to prevent port site recurrence, Kercher et al [10] reported that a wound protector did not significantly diminish the rate of WI at the extraction site; however, it is currently unthinkable to perform LS for malignant diseases without a plastic wound protector, and the significance of plastic wound protectors in terms of WI may need to be investigated in benign diseases.…”
Section: Discussionmentioning
confidence: 98%
“…Plastic wound protectors are used to prevent wound contamination and infection during bowel exposition. However it has been shown that wound protectors are not efficient for this purpose during laparoscopic colectomies [30]. Moreover, wound protectors only protect the abdominal wall from tumor cells seeding, but doe not offer any protection against cells seeding in the abdominal cavity when the colon is extracted through a small incision for proximal bowel preparation.…”
Section: Discussionmentioning
confidence: 99%
“…However, Kercher et al [4] demonstrated that a wound protector did not significantly diminish the rate of wound infection at the bowel resection/anastomotic site. Almost all thoracic surgery for lung cancer are non-contaminated cases; therefore, it is not more useful from a viewpoint of inhibition of wound infection compared to gastrointestinal disease.…”
Section: Commentmentioning
confidence: 97%